Digital Rationality, Anti-Superstition Campaigns, and the Transformation of Religious Authority: A Content Analysis of Ferry Irwandi and Dzawin Nur - Roberto Arieza Martin Purba (Program Pascasarjana IAIN Langsa, 2026)
The rapid expansion of social media has significantly transformed the production, circulation, and legitimation of religious discourse in contemporary society. In Indonesia, one notable phenomenon is the growing influence of digital content creators in reshaping public perceptions of superstition, black magic, shamanism, and other supernatural practices. This study aims to analyze the transformation of religious authority in the digital era through the anti-superstition campaigns of Ferry Irwandi and Dzawin Nur. This research employs a qualitative approach by combining descriptive-analytical and empirical juridical methods. Data were collected from YouTube content, digital audience responses, legal documents, and relevant academic literature. The analysis integrates Theodor Adorno’s Critical Theory, Heidi Campbell’s Digital Religion, and Stig Hjarvard’s Mediatization of Religion. The findings reveal that Ferry Irwandi and Dzawin Nur do not merely expose shamanistic practices empirically; they represent the emergence of new religious authorities operating outside conventional religious institutions. Their authority is not derived primarily from formal religious credentials but from their ability to manage algorithmic visibility, audience engagement, and digital trust. This study contributes to digital religion scholarship by demonstrating that religious authority in contemporary Indonesia is increasingly shaped by algorithmic logic and platform culture, where interpretive legitimacy depends not only on scholarly authority but also on communicative effectiveness within digital ecosystems.